Characteristics of maize cultivars in Africa: how modern are they and how many do smallholder farmers grow? - Abate, T.; Fisher, M.; Abdoulaye, Tahirou; Kassie, Girma T.; Lunduka, R.; Asnake, W.; Marenya, Paswel Phiri (Springer, 2017)
Maize is the most important cereal and most widely cultivated staple that plays a key role in the food security of sub-Saharan Africa (SSA). Although some countries have achieved significant gains in maize productivity, the SSA average yields are far below what could be obtained with improved cultivars under good crop management. Low cultivar turnover is one among many contributing factors to low maize yields in SSA. At present, there is a critical knowledge gap on the identity, number, and age of maize cultivars currently grown by smallholder farmers on the continent.